VBS Stemmer: A vocabulary-based stemmer - Zakeri Rad, Hamed; Tiun, Sabrina; Saad, Saidah (International Journal of Engineering and Technology, 2018)
Stemming is referred to a procedure of reducing all words appearing in different morphological variants to a common form. As a matter of fact, it is considered as a functional way in various areas of information-retrieval work and computational linguistics. In this paper, we introduced the Vocabulary Based Stemmer (VBS) as the alternative solution to the stemming problem for the applications which are based on the semantic relation between words or dictionary based and need valid words. The Vocabulary part of VBS stemmer is generated based on WordNet. To validate the VBS Stemmer, part of â€œCranfield 1400â€ test collection being used, and the result shows significant improvements over the previous stemmers.